TEKNIK PEMIJAHAN IKAN NILA JICA (Oreochromis sp) DI BALAI PERIKANAN BUDIDAYA AIR TAWAR (BPBAT) SUNGAI GELAM PROVINSI JAMBI - Amrullah, Mohd. Yusuf; Turrahmah, Wisa (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2023)
Tilapia is is one of Indonesia's leading commodities that has the potential to be developed in support of national food security and economic security as well as improving people's welfare. The need for tilapia at this time is getting higher, to encourage businesses in the fishery sector which are developed intensively. One type of tilapia that is cultivated in BPBAT Sungai Gelam is JICA (Japan for International Cooperation Agency) Tilapia. JICA tilapia is also resistant to diseases in various water quality and is more resistant to changes in the parent environment than other tilapia. Based on the information obtained, it is necessary to study how the JICA tilapia (Oreochromis sp) spawning techniques can be carried out. The research was conducted from January to February 2023 at the Gelam River Freshwater Aquaculture Fishery Center, Muaro Jambi Regency, Jambi Province. Spawning of JICA  Tilapia (Oreochromis sp) conducted at BPBAT Sungai Gelam, Jambi Province was carried out naturally, where for the comparison of broodstock between males and females with the ratio 1:3. The first spawning stages carried out in spawning of the JICA Tilapia are brood rearing, brood selection, spawning, and larvae harvesting. The total amount of fecundity obtained from the parent sample was an average of 2,741 eggs.